Re-(De)fined Level of Detail for Urban Elements: Integrating Geometric and Attribute Data - Benjamin Boswick; Zachary Pankratz; Matthew Glowacki; Yuhao Lu (Architecture)
The level of detail (LOD) differentiates multi-scale representations of virtual 3D city models; however, the LOD tends to relay primarily the geometric details of buildings. When the LOD extends to other datasets, such as vegetation, transportation, terrain, water bodies, and city furniture, their LODs are not as clearly defined. Despite the general acceptance of this categorization, existing LOD formats also neglect non-geometric attributes. Integrating geometric and attribute data enables geometrically accurate and data-rich 3D models, ensuring that representations are as accurate as possible and that analyses contain as much information as possible. This paper proposes a family of LOD definitions considering both geometric and attribute data based on the geometric complexity and difficulty of obtaining, archiving, processing, and distributing the data. These definitions are intended to apply to all datasets by determining divisions in the LOD typically experienced across urban 3D model elements and their associated datasets, including buildings, vegetation, roads, relief, water bodies, and city furniture. Universally applicable definitions for datasets allow individuals to recreate studies or representations of 3D models to ensure the relevant data are present. These definitions also assist data providers in evaluating their data infrastructure and further strategizing and prioritizing updates or upgrades.